Deletion of the Transcriptional Regulator MucR in Brucella canis Affects Stress Responses and Bacterial Virulence - Sun, Jiali; Dong, Hao; Peng, Xiaowei; Liu, Yufu; Jiang, Hui; Feng, Yu; Li, Qiaoling; Zhu, Liangquan; Qin, Yuming; Ding, Jiabo (Frontiers in Veterinary Science, 2021)
The transcriptional regulator MucR regulates normal growth, stress responses and Brucella virulence, and the expression of various virulence-related genes in smooth-type Brucella strains. However, the function of MucR in the rough-type Brucella canis remains unknown. In this study, we discovered that MucR protein was involved in resistance to heat stress, iron-limitation and various antibiotics in B. canis. In addition, the expression level of various bacterial flagellum-related genes was influenced in mucR mutant strain. Deletion of this transcriptional regulator in B. canis significantly affected Brucella virulence in RAW264.7 macrophage and mice infection model. To gain insight into the genetic basis for distinctive phenotypic properties exhibited by mucR mutant strain, RNA-seq was performed and the result showed that various genes involved in translation, ribosomal structure and biogenesis, signal transduction mechanisms, energy production and conversion were significantly differently expressed in ΔmucR strain. Overall, these studies have not only discovered the phenotype of mucR mutant strain but also preliminarily uncovered the molecular mechanism between the transcriptional regulator MucR, stress response and bacterial virulence in B. canis.